Atypical Ataxia Presentation in Variant Ataxia Telangiectasia: Iranian Case-Series and Review of the Literature - Moeini Shad, Tannaz; Yazdani, Reza; Amirifar, Parisa; Delavari, Samaneh; Heidarzadeh Arani, Marzieh; Mahdaviani, Seyed Alireza; Sadeghi-Shabestari, Mahnaz; Aghamohammadi, Asghar; Rezaei, Nima; Abolhassani, Hassan (Frontiers in Immunology, 2022)
Ataxia–telangiectasia (AT) is a rare autosomal recessive neurodegenerative multisystem disorder. A minority of AT patients can present late-onset atypical presentations due to unknown mechanisms. The demographic, clinical, immunological and genetic data were collected by direct interview and examining the Iranian AT patients with late-onset manifestations. We also conducted a systematic literature review for reported atypical AT patients. We identified three Iranian AT patients (3/249, 1.2% of total registry) with later age at ataxia onset and slower neurologic progression despite elevated alpha-fetoprotein levels, history of respiratory infections, and immunological features of the syndrome. Of note, all patients developed autoimmunity in which a decrease of naïve T cells and regulatory T cells were observed. The literature searches also summarized data from 73 variant AT patients with atypical presentation indicating biallelic mild mutations lead to an atypical phenotype with an increased risk of cancer. Variant AT patients present with milder phenotype or atypical form of classical symptoms causing under- or mis- diagnosis. Although missense mutations are more frequent, an atypical presentation can be associated with deleterious mutations due to unknown modifying factors.